Influence of the starting day of luteal phase stimulation on double stimulation cycles - Fuentes, Ana; García-Ajofrín, Cristina; Romero, Ruth; Castillo, Juan Carlos; Ortíz, Jose A.; Hortal, Mónica; Guerrero, Jaime; Bernabeu, Andrea; Bernabeu, Rafael (Frontiers in Endocrinology, 2023)
Background: Double ovarian stimulation is one of the most used strategies in poor-prognosis patients. There is a high heterogeneity between the studies regarding the execution of this stimulation protocol. The aim of this study was to investigate whether the day on which luteal phase stimulation begins after the first oocyte retrieval affects ovarian response in DuoStim cycles. Methods: This observational and retrospective study included 541 DuoStim cycles between January 2018 and December 2021 in a private fertility clinic. Patients were assigned to 4 groups according to the timing of the onset of luteal phase stimulation after oocyte retrieval (0-2 nd day, 3 rd day, 4 th day and 5 th -6 th day). The primary outcome was the number of oocytes retrieved in the luteal phase in each group. Results: No differences were found between groups in the number of oocytes collected (5.12  3.56 vs. 5.39  3.74 vs. 5.61  3.94 vs. 5.89  3.92; p=0,6), MII or number of follicles. An increase in the duration of stimulation was found when stimulation started on the 4 th day (10.42  2.31 vs. 10.68  2.37 vs. 11.27  2.40 vs. 10.65  2.37 days, p=0,033). A lower number of fertilized oocytes was observed when stimulation began before the fourth day (3.36  2.80 vs. 3.95  2.53 vs. 4.03  2.73 vs. 4.48  3.11; p=0,036). The number of blastocysts was higher when the stimulation started 5-6 days after retrieval (1.82  1.74 vs. 2.13  1.61 vs. 2.33  2.06 vs. 2.91  2.39; p= 0,030). Discussion: The number of oocytes retrieved does not differ depending on the day that stimulation begins. However, oocytes competence in terms of fertilized oocytes and blastulation, appears to be lower when the second stimulation starts before the fourth day after oocyte retrieval.